(untitled) (Indonesian Theological Justice Review, 2024)
Economic inequality remains a significant challenge in Indonesia, where wealth disparities between religious communities, particularly between urban and rural areas, continue to grow. This paper examines economic justice from a theological perspective, focusing on how religious teachings can address wealth disparities within Indonesian society. Drawing on Islamic, Christian, and indigenous perspectives on wealth distribution, the study analyzes how these faiths advocate for economic justice, solidarity, and the ethical responsibility of the rich to care for the poor. The research explores Islamic principles such as zakat (charitable giving) and Christian teachings on wealth and poverty, highlighting the importance of equitable economic practices for social justice. It also examines how religious communities have responded to the growing economic divide through social programs, charity work, and advocacy for fair wages and equitable distribution of resources. The paper argues that theology provides a moral framework for addressing economic injustice and challenges existing socio-economic systems that perpetuate inequality. The study recommends a greater role for religious institutions in advocating for progressive economic policies, promoting ethical business practices, and addressing wealth disparities through social justice initiatives.